Evaluation of nasal challenge with different pollen allergens - Samoliński, Bolesław; Rapiejko, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The authors discuss the specificity of nasal challenge with pollen allergens. The Sets of allergens for nasal challenge are presented.